If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 + -9y + 2y = 7 Combine like terms: -9y + 2y = -7y 21 + -7y = 7 Solving 21 + -7y = 7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + -7y = 7 + -21 Combine like terms: 21 + -21 = 0 0 + -7y = 7 + -21 -7y = 7 + -21 Combine like terms: 7 + -21 = -14 -7y = -14 Divide each side by '-7'. y = 2 Simplifying y = 2
| 10y(2.5+2)+3x=5(3-x) | | 7z+13=16z+8 | | 10y+4=54 | | 10x^2-15x+7=0 | | 4v/27=16*27 | | -13=8x+11 | | 2/3h=28 | | 10m+5=12m-28 | | b/5.4=-3 | | -23(-2)=x | | 5x+4(x-13)=5(x-8) | | V(2v-1)=0 | | 4y(2y-3x)-2x(x-3y)= | | (-9)[3+3]-12= | | 8n+16.2=1.825 | | 22.5+7.5= | | 3/2(x-5)=/6 | | x(3x-5)=(3x+6)(x-3) | | 6(x-8)=12(x+4) | | 3n+5n+2+n= | | (4q+9)(4q+9)=0 | | 4(x+3)=2x+10+2x | | 46/63-5/7 | | 57+57+123+x=360 | | 5+3(y-4)=5(y+3)-y | | -9+6-12= | | 5+7g=54 | | 12x+17x-6+5=-5x+5-6 | | 63=9(2-w) | | 6-4(5p+9)+3(2+p)=-18 | | 3t-18=4(-3-3/4) | | -6x+5(1)=1 |